PENGARUH KUAT TEKAN BETON FC 10,38 MPA DENGAN PENGGUNAAN STEEL FIBER SEJUMLAH 1,5 % DARI AGREGAT KASAR - Anggara, Roni Dwi; Mahardana, Zendy Bima; Bahril Wakhid, Ahmad Fauzan Firulla; Pamungkas, Fatur Rohman Rio; Rohmatin, Silviana; Widiastuti, Liana; Aula, Humidatul (Jurnal Ilmiah Teknik Sipil; Vol 26 No 1 (2022): Jurnal Ilmiah Teknik Sipil, Vol. 26 No. 1, Januari 2022DO - 10.24843/JITS.2022.v26.i01.p04, 2022)
Concrete is a building construction medium that has strong compressive properties and is formed from a mixture of coarse aggregate (coral), fine aggregate (sand), cement and water. The advantages of concrete are that it has strong mechanical properties, excellent durability, and has a dense microstructure. Behind the advantages of concrete, concrete also still has drawbacks. One of the drawbacks is the need to obtain materials. This is due to the excessive exploitation of materials in accordance with the widespread use of concrete so that the reach in obtaining materials becomes more difficult and expensive. In engineering the material requirements used in the research of making concrete this time is to do a combination of steel fibers in the raw material for making concrete. The method used in the concrete research this time is by using the combination method of steel fibers into a mixture of concrete raw materials. Comparison for the manufacture of 3 pieces of normal concrete budgeted Rp. 151,415.00 while the concrete with the addition of steel fibers spent a budget of Rp. 155,312.00. The price difference in the manufacture of concrete is Rp. 3,897.00. In the results of the compressive strength test of the steel fiber combination, the highest value is 11.87 Mpa with an average value of 10.58 Mpa, so that it is able to meet the target of the job mix formula plan of 10.38 Mpa.